The Effect of Sustainable Business Practices on Company Profitability: Evidence From the Asia Sustainability Reporting Rating (ASRRAT) - Putu Rosayanti; I Ketut Suryanawa; I Ketut Sujana; Ni Ketut Lely Aryani Merkusiwati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of sustainable business practices, as measured through the disclosure of economic, environmental, and social aspects based on the Global Reporting Initiative (GRI) Standards 2016, on the profitability of companies participating in the Asia Sustainability Reporting Rating (ASRRAT) during the 2018–2024 period. The growing awareness of sustainability has encouraged companies not only to pursue profit but also to consider their impact on the environment and society as a form of legitimacy and accountability to stakeholders. The study population comprises all companies participating in ASRRAT from 2018 to 2024, with samples selected using a purposive sampling method. The final sample consists of 8 companies, yielding 56 observations. Data were obtained from annual reports and sustainability reports published on the official company websites and the National Center for Corporate Reporting (NCCR). The results reveal that environmental disclosure has a significant positive effect on company profitability, while economic and social disclosures show no significant effect. These findings reinforce both legitimacy theory and stakeholder theory, suggesting that companies can gain social legitimacy and stakeholder trust through genuine environmental commitment.